A Rare Case of Metachronous Clear Cell Ovarian Carcinoma and Thyroid Carcinoma: Clinical and Pathological Insights - Ridwan S; Harsono AB; Suardi D; Kurniadi A; Mantilidewi KI; Hidayat YM (International Journal of Women's Health)
Steven Ridwan, Ali Budi Harsono, Dodi Suardi, Andi Kurniadi, Kemala Isnainiasih Mantilidewi, Yudi Mulyana Hidayat Department of Obstetrics and Gynecology, Faculty of Medicine, Universitas Padjadjaran–Dr. Hasan Sadikin General Hospital, Bandung, IndonesiaCorrespondence: Kemala Isnainiasih Mantilidewi, Department of Obstetrics and Gynecology, Faculty of Medicine, Universitas Padjadjaran–Dr. Hasan Sadikin General Hospital, Bandung, Indonesia, Jl. Pasteur 38, Bandung, West Java, 40161, Indonesia, Email kemala.i.mantilidewi@unpad.ac.idBackground: Clear cell ovarian carcinoma (CCOC) is a type of epithelial ovarian cancer, representing 5– 11% of ovarian cancers. CCOCs tend to occur in the fifth to seventh decades of life, with only 10% of cases occurring in the fourth decade. On the other side, papillary thyroid carcinoma is the most common histology type of thyroid carcinoma and is associated with locoregional spread. Herein, we present a rare case of double-primer ovarian and thyroid cancer, which is a clear cell ovarian carcinoma metachronous with papillary thyroid carcinoma.Case Report: A 47-year-old nulliparous woman presented to our Gynecology Oncology facility with an abdominal mass that had progressively increased in size over the last three months. She had a history of papillary thyroid cancer ten years previously and was treated with radioiodine (I-131). Physical examination revealed an immobile abdominal cystic mass measuring 20 × 18 × 15 cm. Ultrasound imaging revealed a cystic mass with a solid part, measured 16.1 × 10.9 × 12.84 cm, with M4 feature of the IOTA simple rule. CA-125 tumor marker levels were 190.1 U/mL. Ovarian cancer was suspected, and surgical staging with total hysterectomy, bilateral salpingo-oophorectomy, omentectomy, frozen sectioning, and adhesiolysis was performed. Histopathological examination revealed a clear cell ovarian carcinoma.Discussion: Papillary thyroid carcinoma tends to be a locoregional metastasis, whereas distant metastases are rare. Distant metastasis often occurs decades after the primary tumor, with the most common metastatic sites being the lungs and bones. This raises an important clinical question concerning the etiology of the ovarian carcinoma: whether it represents a metastasis from the pre-existing thyroid carcinoma or a distinct primary neoplasm. Determining the precise relationship between these malignancies is crucial for guiding treatment strategies and understanding the biological behavior of the tumors involved. In this case, clear cell ovarian carcinoma arose separately from papillary thyroid carcinoma.Conclusion: Double primer cancer of the ovary and thyroid, which is a clear cell ovarian carcinoma metachronous with papillary thyroid carcinoma, is possible.Keywords: ovarian cancer, thyroid cancer, metachronous